A Creative Arts Approach in Teaching ESL at Ti-Ratana Orphanage, Desa Petaling, Malaysia - Byler, Olivia Turley (2008)
Drawing from Vygotsky's sociocultural learning theory, this research study attempts to explore the potential of the creative arts to teach English as a second language based on the sociocultural theory of learning. The "We Love English!" tuition program utilized the creative arts to teach English as a second language to students living at Ti-Ratana, a Buddhist home for children in Desa Petaling. As a participantobserver, the researcher served as the creative arts director, a volunteer teacher, and a monthly team leader. Research data sources included direct observations made during the lessons; interviews with six volunteer teachers, two program organizers, and one childminder; and analysis of pertinent primary documents. Through comprehensive content analysis, the data were analyzed, categorized, and organized according to specific units of data, which represent inductive and deductive themes in the data. The major findings of this study consist of significant themes that surfaced in all three data sources during analysis. Every effort was made to strengthen the validity and reliability of this study, including data triangulation, the creation of an audit trail, user generalizability, heavy researcher involvement, peer evaluation, thick, rich descriptions, and reflexivity to guard against researcher bias. In short, the data generated from this research study suggest that the creative activities utilized during the "We Love English!" tuition program have the potential to teach English as a second language by creating the necessary environment in which sociocultural learning can take place - namely, by facilitating relationships, promoting social interaction, and fostering zones of proximal development. The creative activities facilitated a friendly, English-speaking environment in which students and volunteer teachers could interact freely and, consequently, build relationships. The relationships between the students and volunteers also appeared to put the students at ease in an English-speaking environment and encourage them to practice English while making language learning more fun. Limitations to the study include lack of time and volunteer turnover. The use of rapid analysis technique following interviews was one method used to mitigate the results of the lack of time, and there were six consistent volunteers, which helped to reduce the effect of volunteer turnover. The findings of this study could contribute to the field of community development and language education. Specifically, this project could serve as a model for community development and educational programs geared towards teaching English as a second language through the creative arts, especially to children at risk. This research study could also provide suggestions related to creating environments conducive for children to interact and build relationships as well as to explore, create, manipulate, and solve problems - ultimately, to reach their maximum learning potential. By creating a comfortable, familiar environment in which sociocultural learning can be realized, a relational, interactive approach to education is critical for maximizing the potential of students, especially children at risk. Therefore, secondlanguage education programs should explore the option of incorporating the creative arts. Education programs that are already based on the sociocultural learning theory could benefit from increased attention to the creative arts. This study also encourages volunteerism, as the findings indicate that dedicated, consistent teachers are critical in order for the creative arts to be effective in fostering relationships and encouraging social interaction. In the end, this research project demonstrates that the creative arts, when utilized in an English tuition program, have the potential to catalyze relationships, increase student interaction, and foster zones of proximal development, all of which contribute to sociocultural learning. It is hoped that further research will provide more conclusive links between the creative arts and second language learning and acquisition.